2014
DOI: 10.1111/bph.12616
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein promotes atherosclerosis by increasing LDL transcytosis across endothelial cells

Abstract: BACKGROUND AND PURPOSEThe retention of plasma low-density lipoprotein (LDL) particles in subendothelial space following transcytosis across the endothelium is the initial step of atherosclerosis. Whether or not C-reactive protein (CRP) can directly affect the transcytosis of LDL is not clear. Here we have examined the effect of CRP on transcytosis of LDL across endothelial cells and have explored the underlying mechanisms. EXPERIMENTAL APPROACHEffects of CRP on transcytosis of FITC-labelled LDL were examined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 63 publications
1
85
0
2
Order By: Relevance
“…Hs-CRP directly increases the transcytosis of LDL across endothelial cells and promotes atherosclerosis due to increasing the LDL retention in vascular walls [30]. This is one of the explanations of the contribution of hs-CRP to thrombotic vascular events such as CHD events.…”
Section: Discussionmentioning
confidence: 99%
“…Hs-CRP directly increases the transcytosis of LDL across endothelial cells and promotes atherosclerosis due to increasing the LDL retention in vascular walls [30]. This is one of the explanations of the contribution of hs-CRP to thrombotic vascular events such as CHD events.…”
Section: Discussionmentioning
confidence: 99%
“…C-reactive protein has also been shown to be involved in many aspects of atherosclerosis [27,[38][39][40], with or without the involvement of modified LDL. CRP inhibited cholesterol efflux from foam cells by inhibiting the expression of ABCA1 and ABCG1 while increasing oxidative stress by promoting activation of ERK1/2 and expression of reduced nicotinamide adenine dinucleotide phosphate oxidase subunits [41].…”
Section: Discussionmentioning
confidence: 99%
“…A complex containing CRP, oxLDL, and β2-glycoprotein I promoted atherosclerosis in diabetic mice by increasing lipid uptake [40]. In ApoE −/− mice, CRP promoted the transcytosis of LDL cross-endothelial cells and vascular wall in a protein kinase C/Src kinase-dependent manner, which resulted in early atherosclerotic changes [38]. CRP bound to eLDL and strongly activated complement pathway [42].…”
Section: Discussionmentioning
confidence: 99%
“…Bian et al [25] found that CRP could directly enhance LDL transcytosis across endothelial cells and promote accumulation of LDL in the subendothelial space of the human umbilical vein wall, via stimulating ROS production and activating protein kinase C (PKC) and Src kinase [73]. PKC phosphorylates Cav-1 at Ser [37], and Src phosphorylates Cav-1 at Tyr [14,74].…”
Section: Crpmentioning
confidence: 99%
“…PKC phosphorylates Cav-1 at Ser [37], and Src phosphorylates Cav-1 at Tyr [14,74]. CRP remarkably increases the expression of Cav-1 and cavin-1 (also known as polymerase I and transcript release factors/PTRF) in membrane raft domains when the caveolae/Cav-1/cavin-1 system participates in the transcellular transport of LDL [25]. These findings suggest that CRP plays an important role in PKC or Src kinase-stimulated transcytosis of LDL and the resultant development of early atherogenesis.…”
Section: Crpmentioning
confidence: 99%